Team Members’ Affective Responses to Patterns of Intragroup Interdependence and Job Complexity - Van Der Vegt, Gerben; Emans, Ben; Van De Vliert, Evert (Journal of Management, 2000)
In this questionnaire study, the relations between the affective reactions of 114 technical consultants and both intragroup interdependence and job complexity were examined. Individual-level task interdependence and job complexity were found to be positively related to individual job satisfaction, team satisfaction, job commitment, and team commitment. Cross-level interactions showed the positive relations between task interdependence and the affective outcomes to be stronger in high outcome interdependent teams than in low outcome interdependent teams. Specifically, a proper match between high task interdependence and high group-level outcome interdependence was found to produce more positive affective responses than “low-high” and “high-low” mismatches. The unfavorable effects of mismatched task and outcome interdependence on job satisfaction and job commitment were found to be mitigated by high levels of job complexity.